The Psychometric Properties of the Student–Teacher Relationship Measure for Omani Grade 7–11 Students - Aldhafri, Said; Alhadabi, Amal (Frontiers in Psychology, 2019)
Development and validation of a 25-item Student-Teacher Relationship Measure is described. It is a self-report measure estimating students’ perceptions of their relationship with teachers. The study was applied among adolescents in grades 7-11 in Oman. The measure was administered in Arabic. In Study 1, findings from exploratory factor analysis for 1035 students indicated the presence of a 2-factor model (academic relation and social relation). In study 2, the confirmatory factor analysis results of 1099 students supported study 1 results. High internal consistency was acquired. STRM was regarded as a reliable and potentially valid measure of the quality of student-teacher relationships.